Continuous crystallization as a downstream processing step of pharmaceutical proteins : a review - Pu, Siyu (2022)
Continuous crystallization has been proposed as the downstream processing step for the purification of pharmaceutical proteins aimed at alleviating the manufacturing bottleneck caused by the limitations of chromatography-based operations at high upstream production titers. Herein we reviewed the current state of research in continuous protein crystallization from which future research directions were identified. While the benefits of batch-to-continuous manufacturing transformation have been long established, progress in continuous protein crystallization lags behind its small-molecule counterpart. The reasons are because the challenging nature of protein crystallization, even when performed in the batch platform, and the lack of well-understood proteins available for thorough study. Nevertheless, successful batch-to-continuous transformations in both mixed-suspension-mixed-product-removal crystallizer and tubular crystallizers (i.e. slug flow, oscillatory baffled flow) have been demonstrated using lysozyme or monoclonal antibody as the model protein. Compared to the batch platform, the continuous platform produces comparable crystallization yield but with higher production capacity (g/h). Strategies to optimize the crystallizer's performance based on modeling and simulation results are also available. Future research should (1) study a wider range of proteins with impurities incorporated in the raw material streams, and (2) adopt advancements in continuous crystallization of small-molecule pharmaceuticals to improve the crystal quality and yield.